First person - Xinrui Wang (The Company of Biologists, 2020)
First Person is a series of interviews with the first authors of a selection of papers published in Disease Models & Mechanisms, helping early-career researchers promote themselves alongside their papers. Xinrui Wang is first author on 'Myh6-driven Cre recombinase activates the DNA damage response and the cell cycle in the myocardium in the absence of loxP sites', published in DMM. Xinrui is a postdoctoral fellow in the lab of John Auchampach at the Medical College of Wisconsin, Milwaukee, WI, USA, investigating cellular and molecular mechanisms of myocardium re-muscularization after injury.